ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA PADA MATERI ARITMETIKA SOSIAL KELAS VII SMP NEGERI 2 TOMA TAHUN PEMBELAJARAN 2020/2021 - Feliks Jurnalistik Zebua (Universitas Nias Raya, 2022)
This research is motivated by the low mathematical problem solving ability of students. This study aims to 1) describe students' mathematical problem solving abilities on social arithmetic material, 2) describe students' difficulties in solving students' mathematical problem solving abilities on social arithmetic materials. This research uses qualitative research with descriptive research methods. Informants in this study were all students of class VII-A, totaling 17 people. The data were analyzed by the steps of data reduction, data presentation and drawing conclusions. The research data collection technique used was a mathematical problem solving ability test and interviews. The results showed that there were still students who had not been able to identify the known data and the data asked in the questions, students had not been able to formulate problems or develop mathematical models, students had not been able to apply strategies in solving social arithmetic problems and students had not been able to interpret or present the final results. which is obtained. So it can be concluded that students' mathematical problem solving ability is still low and students still have difficulty in solving problems related to social arithmetic problems. This is because, students still do not understand the problem and how to formulate or compile a mathematical model of contextual problems. Furthermore, students are still not able to apply the strategies used in solving problems. Researchers suggest that teachers of mathematics subjects pay more attention to the development of students' abilities in solving mathematical problems and students are accustomed to solving problem solving problems.